Enfermedades transmitidas por alimentos contaminados, sus causas, efectos y prevención - Jaramillo Placencia, Joao Alfredo (Machala : Universidad Técnica de Machala, 2022)
Foodborne diseases (FBI) can be caused by pathogens (bacteria, viruses or parasites) and chemical agents (natural toxins, organic contaminants and heavy metals) and are of worldwide importance, because they can cause the consumer to become disabled from his daily tasks, even leading to death, collapsing the health systems. This is due to the little or no application of sanitary regulations in the establishments The main ETAs throughout history have been of animal origin. In Ecuador, the entity that governs establishments that process and distribute food, whether at the national or international level, is the National Agency of Regulation, Control and Sanitary Surveillance (ARCSA), which establishes laws and regulations for obtaining sanitary registration, sanitary hygienic conditions, and the conditions that must be followed for the processes of production, processing, packaging, storage, distribution, transportation and marketing of the product. The purpose of the ARCSA is to guarantee that foodstuffs placed on the market do not cause any harm to the consumer, regardless of their use.
Las enfermedades transmitidas por alimentos (ETAs), pueden ser ocasionada por agentes patógenos (bacterias, virus o parásitos) y agentes químicos (toxinas naturales, contaminantes orgánicos y metales pesados) y son de carácter importante a nivel mundial, porque pueden provocar al consumidor discapacidades de sus labores cotidianas hasta producirle la muerte, colapsando los sistemas de salud. Esto se debe a la poca o nula aplicación de normativas sanitarias en los establecimientos Las principales ETAs a través de la historia han sido de origen animal. En el Ecuador, la entidad que rige sobre los establecimientos que procesan y distribuyen alimentos ya sea a nivel nacional o internacional, es la Agencia Nacional de Regulación, Control y Vigilancia Sanitaria (ARCSA), la cual establece leyes y normativas para la obtención del registro sanitario, condiciones higiénicas sanitarias, y las condiciones que deben seguir para los procesos de producción, elaboración, envasado, almacenamiento, reparto, transporte y comercialización del producto. La ARCSA, tiene como fin garantizar que los alimentos que se comercialicen en el mercado no causen ningún daño al consumidor sin importar el uso que se le dé.
Keywords: ALIMENTO; ETAS; ARCSA; ENFERMEDADES